Amazon forests at the crossroads: pressures, responses and challenges - Jong, W. de; Borner, J.; Pacheco, P.; Pokorny, B.; Sabogal, C.; Benneker, C.; Cano, W.; Cornejo, C.; Evans, K.; Ruíz, S.; Zenteno, M. (IUFRO, 2010)
The Amazon basin and its rich forest has inspired much debate about its natural treasures, potential for economic development and the rights of its populations to exclusive benefits. This debate started in the 1970s and has continued ever since. The chapter points to some of the current key social, occupational and political dynamics in the region and reviews the prime threats affecting Amazon forests and livelihoods. Among these are cattle ranching, soybean production, logging, infrastructure expansion, and the oil and gas industry. These sectors have changed over the years and have adapted to a new economic, political and social climate. The chapter subsequently reviews a series of more recent responses to these threats. Important progress has been made in institutional overhaul, land tenure reform, decentralized government and deregulation and incentives to support sustainable forest use, in particular the newly emerging REDD initiatives. The final part of the chapter provides a balanced assessment of conflicting interests, persisting threats and response options that have achieved positive outcomes suggesting that both old and new challenges require innovative policy action.